Mac-1 blockade impedes adhesion-dependent neutrophil extracellular trap formation and ameliorates lung injury in LPS-induced sepsis - Fang, Jinhua; Ding, Hongguang; Huang, Jiaqi; Liu, Wang; Hong, Tiantian; Yang, Junxian; Wu, Zhiwei; Li, Zhuo; Zhang, Shiying; Liu, Peimin; Fang, Ying; Wu, Jianhua; et al. (Frontiers in Immunology, 2025)
BackgroundSepsis is a common critical condition that can lead to multiple organ injury. Sepsis-induced acute respiratory distress syndrome (ARDS) is frequently an important cause of poor prognosis and is associated with high mortality rates, despite existing therapeutic interventions. Neutrophil infiltration and extracellular traps (NET) are implicated in acute lung injury (ALI) and ARDS following sepsis. As circulating neutrophils infiltrate infected tissues, they come into direct contact with vascular endothelial cells (ECs). Although the ability of NETs to induce endothelial damage is well established, the specific role of direct EC-neutrophil interactions in NET formation and lung injury during sepsis is not fully understood.MethodsIn this study, NET formation was assessed when neutrophils were co-culture with ECs or separated from them and stimulated with phorbol 12-myristate 13-acetate (PMA), lipopolysaccharide (LPS), lipoteichoic acid (LTA), or septic plasma. ResultsWe found that adhesion of neutrophils on ECs is critical in NET formation in response to LPS, LTA, or septic plasma in vitro. Blocking the macrophage-1 antigen (Mac-1) impeded NET formation, while inhibiting P-selectin glycoprotein ligand-1 (PSGL-1) or leukocyte function-associated antigen-1 (LFA-1) did not. This adhesion-dependent NET formation was reliant on the influx of extracellular calcium and peptidylarginine deiminase 4 (PAD4)-mediated citrullination of histone H3. However, Mac-1 blockade did not alter calcium influx. In a murine model of LPS-induced sepsis, Mac-1 blockade reduced NET release, lowered inflammatory cytokine levels, mitigated endothelial damage, and attenuated lung injury.ConclusionOur findings offer insights into the critical role of EC-neutrophil direct contact in NET formation during sepsis and propose Mac-1 as a potential therapeutic target.